Molecular and Clinical Investigations on Portuguese Patients with Multiple acyl-CoA Dehydrogenase Deficiency - Henriques, Bárbara J. (2020)
Background: Multiple Acyl-CoA Dehydrogenase Deficiency (MADD) is a congenital rare metabolic disease with broad clinical phenotypes and variable evolution. This inborn error of metabolism is caused by mutations in the ETFA, ETFB or ETFDH genes, which encode for the mitochondrial ETF and ETF:QO proteins. A considerable group of patients has been described to respond positively to riboflavin oral supplementation, which constitutes the prototypic treatment for the pathology. Objectives: To report mutations in ETFA, ETFB and ETFDH genes identified in Portuguese patients, correlating, whenever possible, biochemical and clinical outcomes with the effects of mutations on the structure and stability of the affected proteins, to better understand MADD pathogenesis at the molecular level. Methods: MADD patients were identified based on the characteristic urinary profile of organic acids and/or acylcarnitine profiles in blood spots during newborn screening. Genotypic, clinical and biochemical data were collected for all patients. In silico structural analysis was employed using bioinformatic tools carried out in an ETF:QO molecular model for the identified missense mutations. Results: A survey describing clinical and biochemical features of eight Portuguese MADD patients was made. Genotype analysis identified five ETFDH mutations, including one extension (p.X618QextX*14), two splice mutations (c.34+5G>C and c.405+3A>T) and two missense mutations (ETF:QO-p.Arg155Gly and ETF:QO-p.Pro534Leu), and one ETFB mutation (ETFβ- p.Arg191Cys). Homozygous patients containing the ETFDH mutations p.X618QextX*14, c.34+5G>C and ETF:QO-p.Arg155Gly, all presented severe (lethal) MADD phenotypes. However, when any of these mutations are in heterozygosity with the known ETF:QO-p.Pro534Leu mild variant, the severe clinical effects are partly and temporarily attenuated. Indeed, the latter destabilizes an ETF-interacting loop, with no major functional consequences. However, the position 155 in ETF:QO is localized at the ubiquinone binding and membrane interacting domain, and is thus expected to perturb protein structure and membrane insertion, with severe functional effects. Structural analysis of molecular models is therefore demonstrated to be a valuable tool to rationalize the effects of mutations in the context of the clinical phenotype severity. Conclusion: Advanced molecular diagnosis, structural analysis and clinical correlations reveal that MADD patients harboring a severe prognosis mutation in one allele can actually revert to a milder phenotype by complementation with a milder mutation in the other allele. However, such patients are nevertheless in a precarious metabolic balance which can revert to severe fatal outcomes during catabolic stress or secondary pathology, thus requiring strict clinical follow-up.